2016
DOI: 10.3390/su8040313
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Countries’ Roles on the International Photovoltaic Trade Pattern: The Complex Networks Analysis

Abstract: Abstract:The expansion of the international PV trade encourages governments to focus on their trade roles in this market, which has increasing impact on their future development of sustainable energy. Thus, an exploration of top traders and their influence on global PV trade pattern is essential as governments seek to develop strategies to improve their global PV market's discourse power. This study introduces the complex network theory to examine top traders whose default would lead to the collapse of trade p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Existing PV product trade studies have mostly been conducted based on the UN Comtrade database, and few of these studies noted re-export and re-import problems in the database 22,28 .…”
Section: Multi-lateral Pv Product Trade and Trade Flow Matrix (Tfm) Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing PV product trade studies have mostly been conducted based on the UN Comtrade database, and few of these studies noted re-export and re-import problems in the database 22,28 .…”
Section: Multi-lateral Pv Product Trade and Trade Flow Matrix (Tfm) Cmentioning
confidence: 99%
“…Studies have been conducted varying from calculating the lifecycle emissions and emission reduction potential of PV products [8][9][10][11][12][13][14][15][16][17][18][19][20][21] to PV product trade patterns and structures 22 to the emissions embodied in the bilateral PV product trade 23 and to the environmental impacts of the PV product trade 13,14,24 . Studies have also been carried out in various countries [15][16][17][18][19][20][21]24 , concluded that PV power generation could indeed help to reduce carbon and local air pollutant emissions obviously.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there were few articles analyzing renewable energy products from the perspective of social networks. Guan et al analyzed the trade status of major trading countries by building an international photovoltaic product trade network from 2000 to 2014 [17]. Ji built a world trade competition network for photovoltaic products and analyzed the intensity and evolution of photovoltaic export trade competition in major countries [18].…”
Section: Introductionmentioning
confidence: 99%
“…As primary energy plays an important role in economic development, countries need to timely adjust energy consumption forms to cope with market fluctuations [1]. Energy strategy [2], energy reserve [3], productivity [4] and geopolitics [3] are crucial for each country engaging in comprehensive energy cooperation. In particular, for primary energy with different strategic status and commodity characteristics, the consumption in different regions is also different, that is, a primary energy consumption directly reflects its strategic status.…”
Section: Introductionmentioning
confidence: 99%